Meningkatkan Literasi Keuangan Syariah Melalui Pelatihan Sistem Operasional Perbankan Syariah Bagi Guru dan Siswa UPTD Sman 5 Parepare - Budiono, I Nyoman; Arifin, Asriadi; Rahma; Harfiana, Fidia (Jurnal Makkareso, 2023)
Sharia banking is a financial institution that has a very important role in supporting the national economy and choosing the same direction for Islamic economic development as envisioned by the Government, but despite this, sharia banking still has several obstacles related to several things, one of which is Sharia bank users are still minimal due to the low level of sharia financial literacy. This community service aims to socialize sharia financial literacy through sharia banking training for UPTD students at SMA Negeri 5 Parepare so that this activity is expected to increase the financial literacy of the participants. The method used is pre test and post test, and this stage consists of preparation, implementation and evaluation stages. The results show that there is a very significant increase in the level of sharia financial literacy in sharia banking products among UPTD students at SMA Negeri 5 Parepare, as in the previous pre-test the average score obtained by students was 52.75, while in the post-test after the material was given it showed the value is 90.5.